DEFLECTIONS AND FREQUENCIES OF NATURAL OSCILLATIONS OF SYSTEMS OF COMPOSITE TWO-LAYER ISOTROPIC PLATES OF THE ROUND SHAPE AT THE CHANGE OF THICKNESS OF ONE OF THE LAYERS - Turkov, Andrey Viktorovich; Abashina, Natalia Sergeyevna; Vetrova, Olga Anatolyevna (Journal of Applied Engineering Science, 2017)
The paper presents a study on the relationship of the maximum deflections and frequencies of the fundamental tone of transverse oscillations of a number of composite two-layer plates of a round shape, rigidly pinched and pivotally supported on the contour. In the course of work we determined the maximum deflectionW0 from the action of the static load and the natural oscillation frequency ω of the composite plates. We defined the proportionality coefficient K. According to the results, we designed the graphs of the maximum deflection change and the frequency of natural oscillations when changing the thickness of one layer of the composite plate.
Keywords: Composite plate; Maximum deflection; Frequency of natural oscillations; Coefficient of plate proportionality